Sb‐Mediated Tuning of Growth‐ and Exciton Dynamics in Entirely Catalyst‐Free GaAsSb Nanowires. Issue 16 (20th January 2023) - Jeong, Hyowon W.; Ajay, Akhil; Yu, Haiting; Döblinger, Markus; Mukhundhan, Nitin; Finley, Jonathan J.; Koblmüller, Gregor
Abstract: Vapor‐liquid‐solid (VLS) growth is the mainstream method in realizing advanced semiconductor nanowires (NWs), as widely applied to many III‐V compounds. It is exclusively explored also for antimony (Sb) compounds, such as the relevant GaAsSb‐based NW materials, although morphological inhomogeneities, phase segregation, and limitations in the supersaturation due to Sb strongly inhibit their growth dynamics. Fundamental advances are now reported here via entirely catalyst‐free GaAsSb NWs, where particularly the Sb‐mediated effects on the NW growth dynamics and physical properties are investigated in this novel growth regime. Remarkably, depending on GaAsSb composition and nature of the growth surface, both surfactant and anti‐surfactant action is found, as seen by transitions between growth acceleration and deceleration characteristics. For threshold Sb‐contents up to 3–4%, adatom diffusion lengths are increased ≈sevenfold compared to Sb‐free GaAs NWs, evidencing the significant surfactant effect. Furthermore, microstructural analysis reveals unique Sb‐mediated transitions in compositional structure, as well as substantial reduction in twin defect density, ≈tenfold over only small compositional range (1.5–6% Sb), exhibiting much larger dynamics as found in VLS‐type GaAsSb NWs. The effect of such extended twin‐free domains is corroborated by ≈threefold increases in exciton lifetime (≈4.5 ns) due to enlarged electron‐hole pair separation in these phase‐pure NWs. Abstract : Free‐standing GaAsSb nanowires are attractive materials with interesting structural and physical properties. Contrasting the typical Sb poisoning effect in conventional vapor‐liquid‐solid growth, entirely catalyst‐free vapor‐solid growth exhibits both surfactant and antisurfactant behavior, with surprising growth enhancements under low Sb content. Tuning Sb incorporation even over narrow compositional range allows remarkable control over microstructure and exciton dynamics.